PENGARUH KOMPENSASI DAN SEMANGAT KERJA TERHADAP INTENSI TURNOVER PADA KARYAWAN PT. JAYA SAMUDRA BERSAMA DI KOTA AMBON - Pieter N. R. Rehatta (Soso-Q : Jurnal Manajemen, 2020)
Research was implemented with objective to know Compensation and Spirit at Work empirically to employee Turnover Intention. Data resources from this research were taken from books references, journal, electronic media and interview. Research was implemented to 44 research subjects of operational employee and used probability sampling technique and distribute questionnaire of Compensation, Spirit at Work and Turnover Intention to Employee of PT. Jaya Samudra Bersama, in Ambon. Data analyses had been used regression analyses technique and used SPSS Statistical 16 for windows program. Results of the research are shows that hypothesis use in this research could be accepted. First hypothesis shows that there is a negative influence between Compensation to Turnover Intention with value of correlation are -0,568; it means that if compensation is more higher, employee Turnover Intention will lower. Second hypothesis shows that there is an influence of loyalty to Turnover Intention with correlation value of -0,345 which means that if loyalty higher then employee Turnover Intention will get lower. Third hypothesis shows that there is an influence between Compensation and Spirit at Work to Turnover Intention with value of r = -0,463 which mean that more higher Employee Compensation and Spirit at Work then will lower employee Turnover Intention. While effective contribution of this research to compensation and Spirit at Work to Turnover Intention of employee in PT. Jaya Samudra Bersama are 46,3%. Keywords: Compensation, Spirit at Work, Turnover Intention